Characterization of the Trans-Epithelial Transport of Green Tea (C. sinensis) Catechin Extracts with In Vitro Inhibitory Effect against the SARS-CoV-2 Papain-like Protease Activity - Carmela Maria Montone (MDPI AG, 2021)
This work describes an untargeted analytical approach for the screening, identification, and characterization of the trans-epithelial transport of green tea (Camellia sinensis) catechin extracts with in vitro inhibitory effect against the SARS-CoV-2 papain-like protease (PLpro) activity. After specific catechin extraction, a chromatographic separation obtained six fractions were carried out. The fractions were assessed in vitro against the PLpro target. Fraction 5 showed the highest inhibitory activity against the SARS-CoV-2 PLpro (IC50 of 0.125 μg mL−1). The untargeted characterization revealed that (−)-epicatechin-3-gallate (ECG) was the most abundant compound in the fraction and the primary molecule absorbed by differentiated Caco-2 cells. Results indicated that fraction 5 was approximately 10 times more active than ECG (IC50 value equal to 11.62 ± 0.47 μg mL−1) to inhibit the PLpro target. Overall, our findings highlight the synergistic effects of the various components of the crude extract compared to isolated ECG.